Comparación de los efectos de tres enjuagues en el manejo de la mucositis oral secundaria al tratamiento de leucemia linfoblástica aguda en niños (2009)
ABSTRACT: The present study was conducted to compare the effects of three mouth rinses in the treatment of oral mucositis induced by chemotherapy in children between 3 and 15 years of age, with acute lymphoblastic leukemia and who were hospitalized at the Pediatric Hemato oncology Pavilion of the San Vicente de Paul University Hospital in the city of Medellin. Methods: three mouth rinses were compared: Triconjugate diphenhydramine, milk of magnesia (magnesium hydroxide) and lidocaine in gel; Sucralfate comprising sucralfate suspended and lidocaine in gel; and a third rinse, called Control consisting of lidocaine in gel; nistatin was added to the mouth rinses to avoid fungal infection. Each group had 3 daily rinses with the assigned mouth rinse and a daily log was made with information related to the severity of mucositis and duration of the episode. The type of study was a quasi-experimental comparative blind design, the sample had 14 cases (triconjugate with 6 cases, 4 in the sucralfate group and 4 in the control group) and collection of the sample was made over a period of 32 months between April 2005 and November 2007. Results and conclusion: no statistically significant differences were found in the severity nor on the length of mucositis among the rinses used by the patients.